2018
DOI: 10.1002/pri.1721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isometric, eccentric, or heavy slow resistance exercises on pain and function in individuals with patellar tendinopathy: A systematic review

Abstract: Findings from isometric exercises can be trusted to guide clinical practice (Grade A), whereas eccentric exercises can be trusted to guide clinical practice in most clinical situations (Grade B). It is recommended that HSR exercises should be applied carefully to individual clinical circumstances (Grade C) and interpreted with care. Isometric exercises appear to be more effective during competitive seasons for short-term pain relief, whereas HSR or eccentric exercises are more suitable for long-term pain reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 24 publications
2
71
0
8
Order By: Relevance
“…[22][23][24][25] Previous systematic reviews have evaluated eccentric and combined concentric/eccentric programmes, but only one review to date has evaluated isometric exercise. 26 This review focused on patellar tendinopathy and concluded that isometric exercise programmes appeared to be effective in short-term pain relief in athletes during the competitive season. Despite their recent popularity, it is unclear if isometric exercise provides superior pain relief when directly compared with other interventions.…”
Section: What Are the New Findingsmentioning
confidence: 99%
“…[22][23][24][25] Previous systematic reviews have evaluated eccentric and combined concentric/eccentric programmes, but only one review to date has evaluated isometric exercise. 26 This review focused on patellar tendinopathy and concluded that isometric exercise programmes appeared to be effective in short-term pain relief in athletes during the competitive season. Despite their recent popularity, it is unclear if isometric exercise provides superior pain relief when directly compared with other interventions.…”
Section: What Are the New Findingsmentioning
confidence: 99%
“…Conventional treatments such as eccentric exercise (EE) programs for the quadriceps tendon, as a part of standard treatment, has demonstrated to have positive results, to the point that many authors have defended this technique as the gold standard for the treatment of tendinopathies [ 9 – 12 ]. A recent systematic review reported that the best exercise for improving knee function and reducing pain in the long term is based on EE and heavy slow resistance exercises (HSR) [ 13 ]. In addition, recent research has focused on minimally invasive techniques (MIT) using needles, with high expectations of success.…”
Section: Introductionmentioning
confidence: 99%
“…Isometric exercises have gained popularity in recent years in the management of other lower limb tendinopathies 11. An isometric exercise programme was compared with an isotonic programme in Australian volleyball and basketball players with patella tendinopathy 12.…”
Section: Introductionmentioning
confidence: 99%